Production and characterization of caffeic acid-loaded microfibrous polycaprolactone mats obtained by electrospinning technology - Moraes Segundo, João de Deus Pereira de; Moraes, Maria Oneide Silva de; Soares, Ana Lorena de Brito; Santos, Gedeandro Gonçalves dos; Silva, Rudyere Nascimento; Almeida, Rosemeire dos Santos; Brito, Walter Ricardo; d’Ávila, Marcos Akira (International Journal of Advanced Engineering Research and Science, 2021)
Microfibrous polycaprolactone (PCL) mats containing caffeic acid were manufactured by electrospinning technology. Electrospun PCL fibers were processed with different concentration of caffeic acid, such as 0.10, 0.25, 0.50, and 1.00% in mass (m/m). The morphologies were observed by scanning electron microscopy (SEM). All produced fibers exhibited random direction and different values of diameters. The caffeic acid did not significantly affect the diameters of the PCL fibers in terms of mean±SD, but some compound concentrations caused the anomaly formation in the electrospun fibers' structure, with the exception of 0.10% CA. Wettability tests in the microfibrous PCL mat with or without caffeic acid showed hydrophobic behavior due to air effect, same with the caffeic acid amount increase. On the other hand, contact angle measurements decrease with the caffeic acid amount increase. The same occurred with the caffeic acid-loaded PCL films. The chemical characterization by FTIR showed the influence of the concentrations of CA in the PCL microfibers, indicating the presence of hydrogen bonds, with the exception of 1.00% CA. We suggest that the 0.10% caffeic acid concentration is the most suitable, mainly due to the absence of anomalies on the surface of the PCL microfibers for future investigations, such as antimicrobial and cytotoxicity tests, drug release, etc.